2017
DOI: 10.1177/0899764017718634
|View full text |Cite
|
Sign up to set email alerts
|

Do Voluntary Associations Show Their Bright or Dark Side Under Adverse Societal Shocks? Evidence From 9/11

Abstract: In this article, we re-assess the relation between association membership and individuals' feelings about immigrants, thereby focusing on possible shifts in this relation in the wake of negative societal shocks (i.e. the 9/11 terrorist attacks). That is, do such events tighten or loosen the connection between association membership and immigrant-intolerance? Using repeated survey data from Flanders (Belgium), our results indicate that there is at best a weak overall connection between association membership an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…For instance, fear of terrorism increased in the US following the 2005 London attacks (Sinclair and Antonius, 2012). Similarly, Geys (2017) shows that Belgians were affected by the 11 September 2001 terrorist attacks in the US. Additionally, because the Paris and San Bernardino attacks occurred in short order, any effects they had on Americans’ attitudes are likely to be cumulative.…”
Section: Datamentioning
confidence: 99%
“…For instance, fear of terrorism increased in the US following the 2005 London attacks (Sinclair and Antonius, 2012). Similarly, Geys (2017) shows that Belgians were affected by the 11 September 2001 terrorist attacks in the US. Additionally, because the Paris and San Bernardino attacks occurred in short order, any effects they had on Americans’ attitudes are likely to be cumulative.…”
Section: Datamentioning
confidence: 99%
“…Studies have also shown that those involved in certain civil society organizations are less ethnocentric (Hooghe, 2003; Laurence, 2020; Lundberg & Abdelzadeh, 2021). Other studies have indicated that sudden shocks such as the 9/11 terrorist attacks did not result in changed levels of tolerance among those involved (Geys, 2017). We therefore expect little change in attitudes among those involved in civil society in the face of a sudden influx of asylum seekers (Geys, 2017).…”
Section: Asylum Seekers Civil Society and Social Trustmentioning
confidence: 99%
“…The purpose of this study is to investigate the extent to which engagement within civil society relates to various forms of social trust among residents in local communities that received varying shares of asylum seekers during the European refugee crisis of 2015 to 2017. Previous studies have investigated how those active within civil society organizations were affected by distant critical events, such as the 9/11 terror attacks in the United States (Geys, 2017). This study investigates the following two core research questions: Were those involved in civil society organizations, in communities that received asylum seekers, more likely to have high levels of trust than those not involved?…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, knowing more about public opinion on migration has always been a crucial issue (for comprehensive overviews, see, Ceobanu and Escandell, 2010;Hainmueller and Hopkins, 2014), but the events in 2015 fueled this discussion. Europe is hardly a continent under "siege," and scholars (Herreros and Criado, 2009;Fitzgerald, 2012;Geys, 2017) and commentators recently argued that hostility to migration is not driven by the numbers of migrants per se, but by perceptions of social cohesion. 2 At the same time, Reuband (2015) suggests in his study of the German nationalist, anti-Islam, farright group "Patriotic Europeans Against the Islamisation of the Occident" that participants of the movement's demonstrations comprise a significant number of "ordinary citizens" who are employed and not socially isolated, but frequently well-embedded in society.…”
Section: Introductionmentioning
confidence: 99%
“…See online at: https://tinyurl.com/ybzqmb72. 4 As discussed more thoroughly below, according to the distinction in Putnam (2000), bridging civic organizations are "outward-looking" and tend to comprise people across diverse social cleavages; bonding clubs are "inward-looking" and tend to be based on more homogeneous memberships, thus reinforcing exclusive identities (see also Coffé and Geys, 2007;Grießhaber and Geys, 2012;Geys, 2017Geys, , p.1204 that it may lead to a potentially normatively negative effect: more skeptical views on migration. Social capital as the general, underlying concept is commonly viewed as a potentially powerful element binding members of a society and, especially given the emphasis on "improved efficiency," comprises a built-in normatively positive impact (see Grießhaber and Geys, 2012;Coffé and Geys, 2007).…”
Section: Introductionmentioning
confidence: 99%